Physiotherapists' experiences of physiotherapy interventions in scientific physiotherapy publications focusing on interventions for children with cerebral palsy: a qualitative phenomenographic approach - Larsson Ingalill; Miller Michael; Liljedahl Kerstin; Gard Gunvor (BMC, 2012)
Abstract Background Physiotherapy research concerning interventions for children with CP is often focused on collecting evidence of the superiority of particular therapeutic methods or treatment modalities. Articulating and documenting the use of theory, instrumentation and research design and the assumptions underlying physiotherapy research interventions are important. Physiotherapy interventions focusing on children with Cerebral Palsy should, according to the literature, be based on a functional and environmental perspective with task-specific functional activity, motor learning processes and Family-Centred Service i.e. to enhance motor ability and improve capacity so that the child can perform the tasks necessary to participate actively in everyday life. Thus, it is important to coordinate the norms and values of the physiotherapist with those of the family and child. The aim of this study was to describe how physiotherapists' experiences physiotherapy interventions for children with CP in scientific physiotherapy publications written by physiotherapists. Methods A qualitative phenomenographic approach was used. Twenty- one scientific articles, found in PubMed, strategically chosen according to year of publication (2001-2009), modality, journals and country, were investigated. Results Three qualitatively different descriptive categories were identified: A: Making it possible a functional-based intervention based on the biopsychosocial health paradigm, and the role of the physiotherapist as collaborative, interacting with the child and family in goal setting, intervention planning and evaluation, B: Making it work an impairment-based intervention built on a mixed health paradigm (biomedical and biopsychosocial), and the role of the physiotherapist as a coach, leading the goal setting, intervention planning and evaluation and instructing family members to carry out physiotherapist directed orders, and; C: Making it normal an impairment-based intervention built on a biomedical health paradigm, and the role of the physiotherapist as an authoritative expert who determine goals, intervention planning and evaluation. Conclusions Different paradigms of health and disability lead to different approaches to physiotherapy which influence the whole intervention process regarding strategies for the assessment and treatment, all of which influence Family-Centred Service and the child's motor learning strategies. The results may deepen physiotherapists' understanding of how different paradigms of health influence the way in which various physiotherapy approaches in research seek to solve the challenge of CP.